Studies of water freezing features in ice cream with starch syrop - Polishchuk, Galyna; Sharahmatova, Tetiana; Breus, Natalia; Bass, Oksana; Shevchenko (Kishenko), Iryna (My University, 2019)
The purpose of the study is to research the process of water freezing in new types of ice cream with starch syrup at certain stages of the technological process. Starch syrup as a degradation product of corn starch is characterized by different values of the dextrose equivalent (DE). Starch syrup is a source of solids, sweetener, cryoprotectants (at high DE) and thickener (for low values of DE). The starch syrups with fundamentally different functional and technological properties are chosen for the study: high glucose-fructose syrup HGFS-98 (DE = 98) and low-sugar starch syrup GFS-30 (DE = 30).
Keywords: морозиво; крохмальна патока; кріоскопічна температура; ice cream; starchy molasses; cryoscopic temperature; кафедра технології молока і молочних продуктів; кафедра технології м’яса і м’ясних продуктів; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки